The Neuroactivation of Cognitive Processes Investigated with SPECT - Daniela Montaldi; Andrew R. Mayes (Behavioural Neurology)
The last ten years have seen the development and expansion of an exciting new field of neuroscientific research; functional mapping of the human brain. Whilst many of the questions addressed by this area of research could be answered using SPECT, relatively few SPECT activation studies of this kind have been carried out. The present paper combines an evaluation of SPECT procedures used for neuroactivation studies, and their comparison with other imaging modalities (i.e., PET and fMRI), with a review of SPECT neuroactivation studies that yield information concerning normal brain function with a particular emphasis on the brain activations produced by memory processing. The paper aims to describe and counter common misunderstandings regarding potential limitations of the SPECT technique, to explain and illustrate which SPECT procedures best fulfill the requirements of a neuroactivation study, and how best to obtain information about normal brain function (whether using normal healthy subjects or patients) and finally to highlight SPECT’s potential future role in the functional mapping of the human brain.